2014
DOI: 10.1177/1941738114528468
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play After Liver and Spleen Trauma

Abstract: Context:Sport-related spleen and liver injuries pose a challenge for the physician. Although rare, these injuries can have serious and even life-threatening outcomes if not accurately diagnosed and managed in a timely fashion. Currently, there are no evidence-based guidelines on duration and intensity of restricted activity and return to play after spleen and liver injury. In addition, there is controversy on follow-up imaging after injury.Evidence Acquisition:PubMed was searched using the terms splenic or spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 53 publications
0
32
0
1
Order By: Relevance
“…Clancy et al reported that patients with higher-grade injuries were more likely to receive follow-up imaging during their period of in-hospital stay. Although CT-based documentation of complete organ healing was once standard of care, follow-up CT is no longer recommended unless clinically indicated [20]. Lynch et al [21] prospectively showed that the average time to sonographic healing in AAST grade I, II, III, and IV injuries was 3, 8, 12, and 21 weeks, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Clancy et al reported that patients with higher-grade injuries were more likely to receive follow-up imaging during their period of in-hospital stay. Although CT-based documentation of complete organ healing was once standard of care, follow-up CT is no longer recommended unless clinically indicated [20]. Lynch et al [21] prospectively showed that the average time to sonographic healing in AAST grade I, II, III, and IV injuries was 3, 8, 12, and 21 weeks, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Restitution of a simple liver laceration and sub-capsular hematoma occurs within 2 to 4 months, whereas complex injuries require up to 6 months [47]. Some experts recommend return to unrestricted activity only after a normalised CT, usually 3 to 6 months after injury [48]. Most authors relate

The recommended period of reduced activity is related to the severity of injury

the recommendation of reduced activity to the severity of injury.…”
Section: Bed Rest and Return To Activitymentioning
confidence: 99%
“…Provide a guideline of return‐to‐play guidelines after splenectomy [21]. Describe the common presentation for blunt bladder trauma, including inability or difficulty voiding, gross hematuria, suprapubic or abdominal pain [22]. •Return to play [21]. Be familiar with the literature and controversy that there is no consensus on return to play, including duration and intensity, after splenic and liver injury.…”
Section: Guidelinesmentioning
confidence: 99%
“…Describe the most common location of pain after a liver injury due to blunt abdominal trauma and the associated referral pain pattern. Provide a guideline for return to play [21]. Describe the Kehr sign and the common presentation after a splenic injury.…”
Section: B Sideline Coverage and Emergenciesmentioning
confidence: 99%
See 1 more Smart Citation